Mapping gas around massive galaxies: cross-correlation of DES Y3 galaxies and Compton-y maps from SPT and Planck. Issue 2 (20th April 2023) - Sánchez, J; Omori, Y; Chang, C; Bleem, L E; Crawford, T; Drlica-Wagner, A; Raghunathan, S; Zacharegkas, G; Abbott, T M C; Aguena, M; Alarcon, A; Allam, S; et al.
ABSTRACT: We cross-correlate positions of galaxies measured in data from the first three years of the Dark Energy Survey with Compton- y maps generated using data from the South Pole Telescope (SPT) and the Planck mission. We model this cross-correlation measurement together with the galaxy autocorrelation to constrain the distribution of gas in the Universe. We measure the hydrostatic mass bias or, equivalently, the mean halo bias-weighted electron pressure 〈 bh Pe 〉, using large-scale information. We find 〈 bh Pe 〉 to be $[0.16^{+0.03}_{-0.04}, 0.28^{+0.04}_{-0.05}, 0.45^{+0.06}_{-0.10}, 0.54^{+0.08}_{-0.07}, 0.61^{+0.08}_{-0.06}, 0.63^{+0.07}_{-0.08}]$ meV cm −3 at redshifts z ∼ [0.30, 0.46, 0.62, 0.77, 0.89, 0.97]. These values are consistent with previous work where measurements exist in the redshift range. We also constrain the mean gas profile using small-scale information, enabled by the high-resolution of the SPT data. We compare our measurements to different parametrized profiles based on the cosmo-OWLS hydrodynamical simulations. We find that our data are consistent with the simulation that assumes an AGN heating temperature of 10 8.5  K but are incompatible with the model that assumes an AGN heating temperature of 10 8.0  K. These comparisons indicate that the data prefer a higher value of electron pressure than the simulations within r 500 c of the galaxies' haloes.